IL‐1RA suppresses esophageal cancer cell growth by blocking IL‐1α. Issue 6 (17th May 2019) - Chen, Sui; Shen, Zhimin; Liu, Zhun; Gao, Lei; Han, Ziyang; Yu, Shaobin; Kang, Mingqiang
Abstract: Background: Interleukin‐1 promotes tumor angiogenesis through VEGF production. The interleukin‐1 receptor antagonist can suppress tumors by blocking this effect. Methods: Immunohistochemistry, WB, and gene sequencing were used to analyze the expression of IL‐1RA in esophageal cancer patients. WB was used to detect the expression of IL‐1RA and interleukin‐1α in esophageal cancer cells. Stable ESCC cell models overexpressing the IL‐1RA were constructed. Their cell functions were tested, and their effects on VEGF were examined. Results: IL‐1RA is downregulated in primary EC tumors, and this downregulation of IL‐1RA is closely related to TNM staging and survival prognosis. The overexpression of IL‐1RA increased the proliferation of KYSE410 EC cells, which have a high level of IL‐1α expression. Overexpression of IL‐1RA in KYSE410 cells promotes a decrease in the expression of VEGF‐A. However, IL‐1RA expression did not cause any changes in EC9706 cells with low IL‐1α expression. Conclusion: IL‐1RA acts as a tumor suppressor, and its deletion promotes tumor progression by increasing VEGF‐A expression in ESCC.